Cell therapy for end-stage liver disease: Current state and clinical challenge - Lin Zhang; Yuntian Deng; Xue Bai; Xiao Wei; Yushuang Ren; Shuang Chen; Hongxin Deng; Yanjie Yin (Chinese Medical Journal)
Abstract. Liver disease involves a complex interplay of pathological processes, including inflammation, hepatocyte necrosis, and fibrosis. End-stage liver disease (ESLD), such as liver failure and decompensated cirrhosis, has a high mortality rate, and liver transplantation is the only effective treatment. However, to overcome problems such as the shortage of donor livers and complications related to immunosuppression, there is an urgent need for new treatment strategies that need to be developed for patients with ESLD. For instance, hepatocytes derived from donor livers or stem cells can be engrafted and multiplied in the liver, substituting the host hepatocytes and rebuilding the liver parenchyma. Stem cell therapy, especially mesenchymal stem cell therapy, has been widely proved to restore liver function and alleviate liver injury in patients with severe liver disease, which has contributed to the clinical application of cell therapy. In this review, we discussed the types of cells used to treat ESLD and their therapeutic mechanisms. We also summarized the progress of clinical trials around the world and provided a perspective on cell therapy.